PANGGUNG KEINDONESIAAN Berebut atau Berbagi? - Mudji Sutrisno S. J. (Sabda: Jurnal Kajian Kebudayaan, 2018)
This article discourses an imagined society along with real practices on mutual respect to become Indonesia. The article explicates the essence of cultural Nusantara in comparison with republic Indonesia. As a case of point of the practices, the articles take the life wisdom of the religions in Indonesia; how the wisdom is relevant to the culture of Nusantara. Besides that, the article gives the illustration of how art workers give their best for Nusantara and respect each other for Indonesia. Lastly, the article questions the willingness of the citizen of Republic of Indonesia: whether or not they are ready to share all resources in the country for the sake of the future generation